Fundamentals of machining processes conventional and nonconventional processes - El-Hofy, Hassan (CRC Press, 2019)
Written by an expert with over 40 years of experience in research and teaching machining and related topics, this new edition textbook presents the principles and theories of material removal and applications for conventional, nonconventional and hybrid machining processes. The new edition is ideal for undergraduate students in production, materials, industrial, mechatronics, marine, mechanical, and manufacturing engineering programs, and also useful for graduate programs related to higher-level machining topics, as well as professional engineers and technicians. All chapters are updated, with additional chapters covering new topics of composite machining, vibration assisted machining and mass finishing operations. Features Presents a wide spectrum of metal cutting, abrasive machining, nonconventional and hybrid machining processes Analyzes the chip formation in machining by cutting and abrasion processes as well as the material removal mechanisms in the nonconventional and the hybrid processes Explains the role of each process variables on its behavior and technological characteristics in terms of material removal, product accuracy and surface quality Portrays the theoretical and empirical formula for removal rates and surface finish in different processes as well as very useful technical data that help in solving and analysis of day-to-day shop floor problems that face manufacturing engineers Clarifies the machinability concept and introduces the general guidelines for machining process selection.